The agricultural waste utilization for exploration of the extracellular enzyme potential of three novel white-rot Basidiomycetes: Fomes fomentarius TMF2, Schizophyllum commune TMF3 and Bjerkandera adusta TMF1 - Ilic N; Davidovic S; Milic M; Rajilic-Stojanovic M; Pecarski D; Ivancic-Santek M; Mihajlovski K; Mihajlovski K
Purpose This study aimed in exploitation of lignocellulosic wastes for the evaluation of the newly isolated white-rot fungal strains enzymatic potential, covered by the circular economy frame. Methods A standard microbiological methods for the isolation of the white-rot fungal mycelia were used, followed by DNA extraction, PCR ampli..cation, and the API ZYM test. The determination of laccase activity was based on the oxidation of guaiacol while the DNS method was used for the hydrolase determination. Results The isolates, belonged to Basidiomycetes, Fomes fomentraius TMF2, Schizophyllum commune TMF3, and Bjerkandera adusta TMF1, could synthesize extracellular laccase and various hydrolase while growing on lignocellulosic waste materials. More speci..cally, for the ..rst time, F. fomentarius TMF2 synthesized laccase using sun..ower meal as a substrate. This substrate could stimulate B. adusta TMF1 for Carboxymethyl cellulase and Avicelase production. The strain TMF1 was able to produce amylase during its growth on brewer's spent grain, which is up to now the best result reported for this activity of any B. adusta strain. Soybean meal was the most potent substrate for stimulating pectinase production by TMF1 and S. commune TMF3. While growing on brewer's spent grain, TMF1 and TMF3 strains produced high levels of xylanase. Spent coffee residues were for the ..rst time tested as a substrate for hydrolase production by selected fungal species.
Keywords: WHITE-ROT FUNGI; SOLID-STATE FERMENTATION; ENZYMES; AGRICULTURAL WASTE